Ophthalmic residents’ surgical training: a study of patient perspective and attitudes in a teaching hospital in India - Siddiqui, Ziya; Abedi, Ali Jafar; Khan, Adeeb Alam; Siddiqui, Atika Javed; Gujral, Gaganjeet Singh (International Journal Of Community Medicine And Public Health, 2017)
Background: An important aim of medical education is to provide sufficient surgical training to residents. Attitudes of patient toward the surgical training of residents and the impact of resident’s participation on patients’ perceptions of care are relatively unknown in India. We therefore undertook this study to assess patient attitudes towards resident cataract surgery training in a teaching hospital. Methods:An anonymous survey was conducted in a teaching hospital on all patients undergoing elective cataract surgery. A questionnaire was developed with inputs from published work, modified according to local needs to record demographic information and elicits patient perspective and attitude towards resident training. Responses of patient’s were graded using a 5-point Likert scale. The data was analysed using SPSS-version 19. Results: Only 35% of surveyed patients selected the most accurate definition of a resident and teaching hospital. The majority (63%) felt “assistance” meant that the resident would be performing parts of surgery, but not the entire procedure. 25% of patients were comfortable having a resident assist their surgery, while only 07% were comfortable with residents performing the entire surgery. Majority (58%) agreed that residents should be involved in the surgical care. Patients demographic background had a significant association with attitudes toward resident involvement in surgery (p<0.05). Conclusions:Results showed varied opinions amongst patients toward the involvement of residents in surgical care. Patient orientation on the resident education process is vital to their perceptions of care and may render them willing to participate in training if they are taken into confidence by the faculty surgeon.